1999
DOI: 10.1016/s0014-5793(99)00897-2
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of angiogenesis through cathepsin B inactivation of the tissue inhibitors of matrix metalloproteinases

Abstract: The tissue inhibitors of matrix metalloproteinases (MMPs), TIMP-1 and TIMP-2, are also angiogenesis inhibitors. Cathepsin B and MMPs are found at sites of neovascularization in pathologies such as cancer and osteoarthritis. Treatment of TIMP-1, TIMP-2, and of a mixture of both inhibitors from human articular chondrocytes with cathepsin B resulted in their fragmentation, whereby they lost their MMPinhibitory and anti-angiogenic activities. Our data suggest that, besides directly participating in tissue destruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(96 citation statements)
references
References 32 publications
2
91
0
3
Order By: Relevance
“…We are currently examining our antisense cathepsin B clones to see if their decreased invasiveness relates to reduction in cathepsin B-mediated activation of plasminogen activators, the proteolytic cascade involved in the degradation of extracellular matrix components. A recent study suggested that besides directly participating in tissue destruction, cathepsin B enhances the activity of matrix metalloproteinases by degrading their inhibitors tissue inhibitors of metalloproteinases-1 (TIMP-1) and TIMP-2 in human articular chondrocytes (Kostoulas et al, 1999). However, whether similar mechanisms are operative in the glioblastoma cells we used in our study is not known.…”
Section: Discussionmentioning
confidence: 85%
“…We are currently examining our antisense cathepsin B clones to see if their decreased invasiveness relates to reduction in cathepsin B-mediated activation of plasminogen activators, the proteolytic cascade involved in the degradation of extracellular matrix components. A recent study suggested that besides directly participating in tissue destruction, cathepsin B enhances the activity of matrix metalloproteinases by degrading their inhibitors tissue inhibitors of metalloproteinases-1 (TIMP-1) and TIMP-2 in human articular chondrocytes (Kostoulas et al, 1999). However, whether similar mechanisms are operative in the glioblastoma cells we used in our study is not known.…”
Section: Discussionmentioning
confidence: 85%
“…Finally, cathepsin B and metalloproteases may form a proteolytic cascade. For instance, it has been shown that cathepsin B inactivates tissue inhibitors of membrane metalloprotease, thus leading to increased metalloprotease activity (56). Furthermore, there is precedence for growth factor activation as a result of cleavage by cathepsin B (57), and cathepsin B has been shown to cause peptide cleavage at the same sites as membrane metalloproteases (58).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, strong immunostaining of cathepsin B was observed in rat brain microvascular endothelial cells as they formed capillary tubes in vitro (Keppler et al, 1996). Since cathepsin B was shown to be an inhibitor of TIMPs (Kostoulas et al, 1999) and TIMPs are inhibitors of angiogenesis, cathepsin B could also stimulate angiogenesis, which has an important role in tumor spread. It has been reported in the host results in the enhanced adhesion of uPAR-bearing endothelial cells to the ECM protein vitronectin due to the loss of PAI-1, which adversely affects cell motility and resultant neovascularization (Gutierrez et al, 2000).…”
Section: Cathepsin B and Upar Sirna Suppresses Intracranial Tumor Growthmentioning
confidence: 97%